2020
DOI: 10.1002/adma.202003382
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation‐Induced Emission Luminogens Married to 2D Black Phosphorus Nanosheets for Highly Efficient Multimodal Theranostics

Abstract: Inspired by the respective advantages of aggregation‐induced emission (AIE)‐active photosensitizers and black phosphorus nanomaterials in cancer treatment, the facile construction of novel AIE photosensitizers married to 2D black phosphorus nanosheets and their application for multimodal theranostics are demonstrated. The developed nanomaterial simultaneously possesses distinctive properties and multiple functions including excellent stability, good biocompatibility, intensive fluorescence emission in the NIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 57 publications
0
95
0
Order By: Relevance
“…The two kinds of moiety are bridged through different units such as phenyl and thiophene groups to regulate the molecular electron effect. As shown in Table 1 (AIE–PSs 9 – 19 ), most of the AIE (donor)-acceptor AIE–PSs are constructed in this way and exhibit good performance [ 42 , 56 , 58 , 59 ]. For instance, 10 and 12 , respectively, showed strong AIE with the emission enhancement up to 290-fold and 34-fold, large two-photon absorption cross-section up to 477 and 303 GM, respectively, and highly specific targeting to mitochondria in living cells with good biocompatibility [ 55 ].…”
Section: Aie-pss Based On Energy Transfer (Type Ii) Mechanismmentioning
confidence: 99%
“…The two kinds of moiety are bridged through different units such as phenyl and thiophene groups to regulate the molecular electron effect. As shown in Table 1 (AIE–PSs 9 – 19 ), most of the AIE (donor)-acceptor AIE–PSs are constructed in this way and exhibit good performance [ 42 , 56 , 58 , 59 ]. For instance, 10 and 12 , respectively, showed strong AIE with the emission enhancement up to 290-fold and 34-fold, large two-photon absorption cross-section up to 477 and 303 GM, respectively, and highly specific targeting to mitochondria in living cells with good biocompatibility [ 55 ].…”
Section: Aie-pss Based On Energy Transfer (Type Ii) Mechanismmentioning
confidence: 99%
“…prepared AIE-active photosensitizer married with 2 dimensional (2D) black phosphorus and applied it to multimodal theragnosis of tumour. 74 Recently, they prepared a one-for-all AIEgen for PDT, photothermal therapy, photoacoustic imaging, which could precise reveal tumour locations and completely eliminate tumour. 75 Furthermore, Ding et.…”
Section: Materials Chemistry Frontiers Accepted Manuscriptmentioning
confidence: 99%
“…27 Considering all these benefits, a variety of photothermal antibacterial agents have been developed to boost the development of PTT, such as gold-based nanomaterials, 28,29 copper-based chalcogenide nanomaterials, 30 carbon-based nanomaterials, 31 polymer nanoparticles, [32][33][34] and black phosphorus. 35 Among them, copper-based materials have attracted much attention due to their low cost and stable photothermal conversion performance. 30,36 It is widely reported that copper salts possess intrinsic antibacterial and antiviral capabilities, presumably due to the generation of reactive oxygen species (ROS) via Fenton-like reactions.…”
Section: Introductionmentioning
confidence: 99%